REPUTATION, INC.: THE INDUSTRIALIZATION OF DIGITAL SELF PRESENTATION AND ONLINE PRIVACY - Draper, Nora (AoIR Selected Papers of Internet Research, 2015)
In the context of a new information environment that lacks both appropriate regulation and shared social norms, a collection of for profit companies has emerged over the past two decades to help support and define personal privacy for the digital age. In the larger project from which this paper draws, I trace the complex and evolving approaches these actors have towards notions of identity construction, authentic self-presentation, visibility, and value creation in an online environment. In this paper, I focus specifically on the role this industry has played in reflecting and shaping the norms that guide contemporary approaches to digital self-presentation. I observe how industrial practices have mobilized and destabilized collectively understood terms, redefining them in ways that reflect the changing economic, social, and political realities of an evolving digital environment. In particular, I examine how this industry has positioned the terms “autonomy” and “authenticity,” defining and redefining them at key moments over the past two decades.